TEACHER’S STRATEGIES IN TEACHING ENGLISH SPEAKING SKILL FOR AUTONOMOUS LEARNERS (A CASE STUDY OF INDONESIAN MIGRANT WORKERS IN PENANG - MALAYSIA) - HAKIM, M. ARIF RAHMAN; KHOIRUNNISA, KHOIRUNNISA; FADLI, AKHMAD; ADNAN, NUR ILIANIS (Linguists : Journal of Linguistics and Language Teaching, 2023)
This study was carried out to investigate strategies used by the teacher in teaching English, speaking competency, for autonomous learners at English Academy Bengkulu Malaysia, an English class program for Indonesian migrant workers. Specifically, it was conducted to identify whether the strategies were proper to be applied in teaching students whose profession as migrant workers. The qualitative method and case study approached were applied in conducting this research. Thirty workers and a teacher were selected as the participants. A series of interview, classroom observations, and video- recordings are done by the researchers to collect the data. Then they were analysed by using Miles and Huberman’s framework of qualitative analysis. The result of the study shows that to arrange proper strategies in teaching Indonesian migrant workers in Malaysia, teacher had to understand their characteristic first. In this study, the researchers found that most of the students had the characteristics of autonomous learners as follows; responsive [AL-BR], independent [AL-BI], well- motivated [AL-BWM], and self-aware [AL-BSA]. Based on these four characteristics, the teacher was able to arrange the strategies that proper to be practiced in the classroom. The strategies used by the teacher in teaching English speaking skill for Indonesian migrant workers were interactive techniques, grammar translation method, cooperative learning, direct instruction, and diary- writing. Students' activities in class as a result of the teacher's strategies were related to and consistent with the teacher's beliefs about autonomous learners and their characteristics. In other words, the strategies are effective, compelling, and appropriate for use in a class with autonomous learners.